Validity Profile and Practically Biological Teaching Structures Based on Local Potenties BIOLA PJBL High Level and Enrichment Program - Tuapattinaya, Prelly Marsell J; Papilaya, Pamella Mercy; Sinay, Hermalina; Awan, Ali (KnE Social Sciences, 2024)
Biology based on local potential Bioecology (BIOLA) PjBL High Level, is a promoter of a valid and practical enrichment program for SMAN pupils in Saparua Island. Products were developed in the form of RPPs, teaching materials, and Students Project Activity Sheets (LAPPD). This research includes a type of research and development that refers to a modified 4D development model that has three phases: (1) define, (2) design, and (3) develop. Research instruments use validation lifts and practicality lifts. Validation of learning instruments using a validation lift evaluated by four instruments expert validators consisting of two lecturers and two practitioners namely Biology subjects teachers. The practicality test of the learning instruments was evaluated using the response lift by the teacher and the pupil and the implementation of learning process by the teacher as an observer. The method used is descriptive statistics to obtain averages and percentages. The results of the validity analysis of the learning instruments using the Ideal Baku deviation (SBI), showing a rating of 3.93 with a very good category. Results of the analysis of implementation of the PJBL high level Biola instruments in the learning process by the observer and student responses in sequence showed 91% and 89.20% with the very practical category. So, it can be concluded that the BIOLA-PjBL High Level based biology learning instruments that has been developed is valid and practical for use as well as useful for teachers and pupils. Keywords: Innovative teaching instruments, local potential, bioecology, PJBL High Level, enrichment program